Extranodal natural killer/T‐cell lymphoma in an 11‐year‐old child. Issue 12 (3rd November 2020) - Ninchoji, Takeshi; Fujimura, Junya; Uemura, Suguru; Yamamoto, Nobuyuki; Nozu, Kandai; Iijima, Kazumoto
Abstract: Extranodal natural killer/T‐cell lymphoma (ENKTL) is difficult to identify and diagnose appropriately. Positron emission tomography imaging is a crucial method that leads to precise diagnosis. A proper regimen including stem cell transplantation would possibly improve prognosis of advanced ENKTL. Abstract : Extranodal natural killer/T‐cell lymphoma (ENKTL) is difficult to identify and diagnose appropriately. Positron emission tomography imaging is a crucial method that leads to precise diagnosis. A proper regimen including stem cell transplantation would possibly improve prognosis of advanced ENKTL.